Perancangan Shopping Center dengan Pendekatan Arsitektur Neo Vernakular di Kota Padangsidimpuan - Agil Akmal Yusuf; Dwi Lindarto Hadinugroho (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The construction of a shopping center in Padangsidimpuan aims to meet the growing needs of the urban population for modern and practical shopping facilities. Urban residents' interest in shopping centers, known as malls, is considered an appropriate choice, resulting in these places always being bustling with visitors from diverse backgrounds. To preserve traditional design elements, one of the steps taken is to implement the Neo-Vernacular design approach. This architectural approach has the ability to adapt well across various eras and building types. Shopping and entertainment centers are an excellent choice for applying the Neo-Vernacular architecture concept. Additionally, shopping and entertainment centers will become more appealing if they can reflect local historical and cultural values. In this way, the mall can become a new and proud icon for Padangsidimpuan